The complete genome sequence of the phytopathogenic fungus Sclerotinia sclerotiorum reveals insights into the genome architecture of broad host range pathogens - Derbyshire, Mark; Denton-Giles, Matthew; Hegedus, D.; Seifbarghy, S.; Rollins, J.; van Kan, J.; Seidl, M.; Faino, L.; Mbengue, M.; Navaud, O.; Raffaele, S.; Hammond-Kosack, K.; et al. (Oxford University Press, 2017)
Sclerotinia sclerotiorum is a phytopathogenic fungus with over 400 hosts including numerous economically important cultivated species. This contrasts many economically destructive pathogens that only exhibit a single or very few hosts. Many plant pathogens exhibit a “two-speed” genome. So described because their genomes contain alternating gene rich, repeat sparse and gene poor, repeat-rich regions. In fungi, the repeat-rich regions may be subjected to a process termed repeat-induced point mutation (RIP). Both repeat activity and RIP are thought to play a significant role in evolution of secreted virulence proteins, termed effectors. We present a complete genome sequence of S. sclerotiorum generated using Single Molecule Real-Time Sequencing technology with highly accurate annotations produced using an extensive RNA sequencing data set. We identified 70 effector candidates and have highlighted their in planta expression profiles. Furthermore, we characterized the genome architecture of S. sclerotiorum in comparison to plant pathogens that exhibit “two-speed” genomes. We show that there is a significant association between positions of secreted proteins and regions with a high RIP index in S. sclerotiorum but we did not detect a correlation between secreted protein proportion and GC content. Neither did we detect a negative correlation between CDS content and secreted protein proportion across the S. sclerotiorum genome. We conclude that S. sclerotiorum exhibits subtle signatures of enhanced mutation of secreted proteins in specific genomic compartments as a result of transposition and RIP activity. However, these signatures are not observable at the whole-genome scale.